Assessment of the Birmingham vasculitis activity score in patients with MPO-ANCA-associated vasculitis: sub-analysis from a study by the Japanese Study Group for MPO-ANCA-associated vasculitis. Issue 2 (March 2014) - Yumura, Wako; Kobayashi, Shigeto; Suka, Machi; Hayashi, Taichi; Ito, Satoshi; Nagafuchi, Hiroko; Yamada, Hidehiro; Ozaki, Shoichi
Abstract Objectives. In the study cohort enrolled in a prospective open-label, multicenter trial conducted by the Japanese Study Group for MPO-ANCA-associated vasculitis (JMAAV), we conducted this sub-analysis to establish the validity of the Birminghan vasculitis activity score (BVAS) for Japanese patients with MPO-ANCA-associated vasculitis. Methods. We recorded the BVAS at the time of diagnosis, at 6 weeks after the diagnosis, and at 3, 6, 9, 12, 15 and 18 months after the diagnosis in this study. Results. The most frequently involved organs in the patients were the lungs, kidneys and the nervous system. The kidney (BVAS; new/worse 69.2 %, persistent 40.4 %), general (BVAS; new/worse 67.3 %, persistent 53.8 %), chest (BVAS; new/worse 36.5 %, persistent 46.2 %) and nervous system (BVAS; new/worse 38.5 %, persistent 25.0 %) were the organ systems most frequently involved by the disease at the baseline. The BVAS for new/worse disease decreased immediately after induction therapy, while improvement of the BVAS for persistent disease after therapy differed among the organ systems. Conclusions. BVAS was demonstrated to be a valuable guide for selection of the optimal treatment. Thus, BVAS was also found to be a useful tool in Japanese patients for the assessment of disease activity and degree of organ damage in patients with MPO-ANCA-associated vasculitis.